Sexual Abuse and Childhood Pregnancies an Analytical Evaluation of 111 Case - Aydın, Berna; Turla, Ahmet; Dündar, Cihad (The Bulletin of Legal Medicine, 2015)
Objective: The purpose of this study was to investigate characteristics of abuse suffered by children exposed to sexual abuse resulting in pregnancy, the features of those pregnancies, and the scale of the psychological impact involved. Materials and Methods: Patient records for 111 children under the age of 18 who became pregnant as a result of sexual abuse and were referred for reports and examination to the Ondokuz Mayıs University Mdical Faculty Forensic Medicine Department over a 6-year period were investigated. Results: Mean age at first pregnancy was 14.51.3 (11-17) years. Of the victims, 41.4% reported that sexual abuse took place due to threats, deception or compulsion, 68.5% reported abuse was repeated, 13.5% fell pregnant as a result of abuse by a member of the family, approximately half of the pregnant children gave birth, approximately half of the babies were placed in care away from the mother and three were adopted. Psychological pathologies due to their experiences developed in half the pregnant victims of abuse, and threats/deception, repeated abuse and presence of incest were identified as risk factors for psychological pathology. Conclusion: Victims of abuse who fall pregnant are exposed to long-term and permanent effects, not just in terms of physical and mental health, but also in the social sphere, such as economic dependence. It should therefore be remembered that these adverse effects in victims of sexual abuse presenting in the acute period can be overcome through the administration of emergency contraception. In victims presenting after the acute period, however,...